Factors Affecting Bad Nutrition In Children : A Systematic Review - rambe, nova; Suci Wulandari (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
Malnutrition is a medical condition caused by inadequate intake, which is usually associated with malnutrition due to insufficient food intake, poor absorption, or excessive loss of nutrients. Malnutrition is caused by a lack of protein, calories or total energy. In toddlers, malnutrition is characterized by resistance to growth hormone (GH). This criterion used original articles, published in English and Indonesian. Articles published in the last 10 years. The review method used systematic review using PRISMA For Systematic Review, which was obtained from the Pubmed, Ebsco, Wiley database. It aims to be able to find out the factors which affect malnutrition in infants.